3D printing technology based on nanometer materials in mechanical automation processing. Issue 1 (20th July 2021) - Yao, Jin; Zou, Fangli; Feng, Jing; You, Rentang; Sun, Jiaxing; Zhang, Xiaofei; Xiang, Yongzhi
Abstract: With the rapid development of various industries, the machinery manufacturing industry has been constantly carrying out reform and innovation, among which the introduction and use of technology is constantly increasing, so as to promote the development level of the machinery manufacturing industry. As the most cutting-edge and most potential technology, 3 D printing technology is an important direction of the development of mechanical automation processing. The purpose of this paper is to study the application of 3 D printing technology based on nanomaterials in automatic machining. This paper first introduces the basic concept and working principle of 3 D printing technology, and analyzes the types of 3 D printing technology. Then the classification and preparation of nanomaterials are introduced. This paper also studies the application of 3 D printing technology based on nanomaterials in mechanical automation. The experimental materials in this paper select gold nanoparticles of nanomaterials, and use SLS technology of 3 D printing to degrease and sintering gold nanoparticles. In this paper, the performance of the embryo was tested through two processes of degreasing and sintering, and the experimental results showed that the application of 3 D printing technology based on nanomaterials in mechanical automatic processing has certain practical significance. In this paper, the degreasing rate of the billet at different degreasing temperature is analyzed. When the degreasing temperature is 500 °C, the degreasing rate of the billet reaches 94%.